Aspects Influencing Maize Farmers’ Involvement in Agricultural Extension Training in Zambia - Mwansa, Prof. Bupe (American Journal of Agriculture, 2023)
Purpose: The purpose of this study is to investigate the major Aspects influencing maize farmers"Ÿ contribution in the agricultural extension training programmes in Zambia. Methodology: The paper used a desk study review methodology where relevant empirical literature was reviewed to identify main themes and to extract knowledge gaps. This involved an in-depth review of studies related to the major aspects influencing maize farmers' contribution in the agricultural extension training programmes. Three sorting stages were implemented on the subject under study in order to determine the viability of the subject for research. Findings: According to the study's findings, Zambian participation in the agricultural extension-training program was low. Institutional obstacles such a lack of accessibility to training facilities, subpar facilities, and coordinators with weak coordination abilities have an impact on farmers in Zambia. Unique Contribution to Theory Policy and Practice: The government should establish training facilities close to farmers as a means of promoting more participation. Due to the quick development of agricultural technology, agricultural extension staff in Zambia should also urge farmers to take part in training programs. To enable them to find the time for the training programs, farmers should be made aware of the advantages of cultivating maize.